Wastewater and Water Quality - Taner Yonar (IntechOpen, 2018)
Water is accepted as the most important source of life. It is assumed that life began in water and spread from there to the whole world. But water has been polluted anthropogenically since the beginning of the industrial revolution in the late 19th century. At the end of the 20th century, most water sources cannot be used for aquaculture, irrigation, and human use. Therefore, for sustainable development, we have to protect our water sources on Earth, because it's the only planet we have!
English
Keywords: Physical Sciences; Engineering and Technology; Technology; Wastewater Engineering; Environmental Engineering